2016
DOI: 10.1038/srep31712
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure matters: breaking down the barriers with single crystalline silicon as negative electrode in Li-ion batteries

Abstract: Silicon-based microelectronics forms a major foundation of our modern society. Small lithium-ion batteries act as the key enablers of its success and have revolutionised portable electronics used in our all everyday’s life. While large-scale LIBs are expected to help establish electric vehicles, on the other end of device size chip-integrated Si-based μ-batteries may revolutionise microelectronics once more. In general, Si is regarded as one of the white hopes since it offers energy densities being ten times h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
4
30
0
1
Order By: Relevance
“…16). Diffraction patterns for the crystalline and amorphous Si should be clearly distinguishable, as shown in the work of Sternad et al [31]. However, in the present study, the FFT images showed both types of diffraction patterns (i.e.…”
Section: Tem and Eds Analyses Of Fib-irradiated Samplesupporting
confidence: 58%
“…16). Diffraction patterns for the crystalline and amorphous Si should be clearly distinguishable, as shown in the work of Sternad et al [31]. However, in the present study, the FFT images showed both types of diffraction patterns (i.e.…”
Section: Tem and Eds Analyses Of Fib-irradiated Samplesupporting
confidence: 58%
“…doping of Si thin films, 50 usage of binary Si thin film systems such as Mg-Si, 46 Ni-Si 51 or Si-Al, 52 structuring of electrodes, 45,49,53,54 surface modifications or coatings 42,47,55 as well as multilayer systems. [56][57][58] In this work, the focus is set on the manufacturing of Si-based thin film electrodes as well as their designed surface and structure modification by amorphous carbon layers to increase the mechanical stability and, thus, the electrochemical performance.…”
Section: <>mentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46][47][48] Thin film electrodes are of special interest for usage in micro-batteries powering miniaturized electronic devices, for example for medical applications. 2,49 A schematic illustration of a possible set-up of an allsolid-state (micro-) battery is depicted in Figure 1a, in which a solid electrolyte can be used between the positive and negative thin film electrodes.…”
mentioning
confidence: 99%
“…However, the complicated nanostructures circumvent the problem only on the laboratory scale due to expense of the material production and difficulties in the production scale-up 6 . Some studies have managed to successfully employ micrometer sized silicon with reasonable mass loadings 13,14 . Another viable option is to utilize mesoporous silicon (PSi) material that can accommodate most of the volumetric changes and make the anode more robust 15,16 .…”
mentioning
confidence: 99%